Theory of subjectivity and psychotherapy: A proposal from the Historical-Cultural Perspective - Rodriguez-Camejo, Jeremy Swan; García-Ramos, Tania; Santiago-Estrada, Sara (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
This article discusses the value of the theory of subjectivity of the Cultural Historical Perspective (CHP) for the field of clinical psychology and psychotherapy. In this discussion we explore how the translation and diffusion of Vygotsky’s work in the west was affected by historical and ideological factors that prevented the CHP from extending its reach to the field of clinical psychology. Additionally, we discuss the theory of subjectivity, psychotherapy and qualitative epistemology proposed by Gonzalez Rey as an alternative that could be the link between the CHP and clinical psychology. Finally, we discuss aspects that need to be further elaborated in Gonzalez Rey’s theory as part of its implementation in the clinical field.